2014
DOI: 10.1002/anie.201405770
|View full text |Cite
|
Sign up to set email alerts
|

A Biomimetic Synthesis of (±)‐Basiliolide B

Abstract: A highly diastereoselective and practical biomimetic total synthesis of (±)-basiliolide B has been achieved through the study of the two proposed biosynthetic pathways (O-methylation and O-acylation) for the unprecedented 7-methoxy-4,5-dihydro-3H-oxepin-2-one (C ring). The synthesis featured a cyclopropanation/ring opening strategy for establishing the stereogenic centers at C8 and C9, a biomimetic 2-pyrone Diels-Alder cycloaddition for the synthesis of the ABD ring system, and finally a highly efficient biomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Capitalizing on this advantage, UCL nanoparticles (UCNPs) have emerged as nanotransducers for the development of photocontrolled delivery systems. [113][114][115][116] UCNPs typically consist of a rare-earth metal fluoride lattice doped with lanthanide ions, such as ytterbium (Yb 3+ ), thulium (Tm 3+ ), or erbium (Er 3+ ). [117][118][119][120] They are excited in the NIR range and have tunable fluorescence emission depending on the dopant types and their concentrations.…”
Section: Ucnp-based Nanomaterials For Photoexcited Drug Releasementioning
confidence: 99%
“…Capitalizing on this advantage, UCL nanoparticles (UCNPs) have emerged as nanotransducers for the development of photocontrolled delivery systems. [113][114][115][116] UCNPs typically consist of a rare-earth metal fluoride lattice doped with lanthanide ions, such as ytterbium (Yb 3+ ), thulium (Tm 3+ ), or erbium (Er 3+ ). [117][118][119][120] They are excited in the NIR range and have tunable fluorescence emission depending on the dopant types and their concentrations.…”
Section: Ucnp-based Nanomaterials For Photoexcited Drug Releasementioning
confidence: 99%
“…Colloidal particles that can respond to stimuli on demand at the targeted sites or at specific time points have received extensive attention due to the versatility in biomedical fields, including gene/drug delivery, biosensors, and bioreactors. [1][2][3] The stimuli-response can be divided into internal stimuli (e.g., redox, [4] pH, [5] and enzyme) [6] and external stimuli (e.g., light, [7,8] In this study, bovine serum albumin (BSA) doped-MnCO 3 sub-micrometer particles are used as sacrificial template. The carboxyl and benzyl bromide groups of ortho-nitrobenzyl derivative 4-bromomethyl-3-nitrobenzoic acid (BNBA) can react with the amine groups of BSA to form the cross-linking points.…”
Section: Introductionmentioning
confidence: 99%
“…For example, by integrating plasmonic nanoparticles in the shell, Ott et al [7] reported light-addressable and degradable silica capsules which can deliver cargo to the cytosol of cells via photo thermal heating. Min et al [8] reported a novel near-infrared light-activated nanoplatform to realize the remote control of antitumor prodrug activation. They demonstrated that by combining a photoactivatable platinum prodrug with silica-coated upconversion-luminescent nanoparticles, the prodrug complex can be activated upon near-infrared light illumination, which efficiently induced potent antitumor cytotoxcity in both cisplatin-sensitive and resistant tumor cells.…”
mentioning
confidence: 99%
“…[19] Ultimately it was discovered that heating a toluene solution of the methoxycarbonylated pyrone for 4 days at 100 °C smoothly elicited a [4+2] cycloaddition in high yield (90%) and without the need for high dilution. This process forges four stereocenters in a single operation (Scheme 1).…”
mentioning
confidence: 99%
“…Bicycles 12 and 13 appear to arise from favourable chair-like transition states as opposed to the alternative, boat-like structures shown (Figure 2). Owing to a lack of allylic strain, which has benefitted related intramolecular pyrone/alkene cycloadditions, [19] the pyrone group in this system does not have a biasing element favouring a given pyrone rotamer. [20] The gram- scale synthesis of 12 only became possible after significantly exploring a number of individual cycloaddition reactions, substrates, and conditions (Table 1).…”
mentioning
confidence: 99%